2014
DOI: 10.1016/j.gene.2013.10.071
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of two glutathione peroxidase genes of Panax ginseng and their expression analysis against environmental stresses

Abstract: a b s t r a c t a r t i c l e i n f oGlutathione peroxidases (GPXs) are a group of enzymes that protect cells against oxidative damage generated by reactive oxygen species (ROS). GPX catalyzes the reduction of hydrogen peroxide (H 2 O 2 ) or organic hydroperoxides to water or alcohols by reduced glutathione. The presence of GPXs in plants has been reported by several groups, but the roles of individual members of this family in a single plant species have not been studied. Two GPX cDNAs were isolated and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…The plant GPX genes are well known to be involved in responses to various environmental stresses29313236. Therefore, we analysed the promoter regions of all 13 GhGPX genes to find their putative cis -acting regulatory elements involved in stress and hormone signaling (Table 3) by using PlantCARE software42.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant GPX genes are well known to be involved in responses to various environmental stresses29313236. Therefore, we analysed the promoter regions of all 13 GhGPX genes to find their putative cis -acting regulatory elements involved in stress and hormone signaling (Table 3) by using PlantCARE software42.…”
Section: Resultsmentioning
confidence: 99%
“…GPX genes from a range of plant species, such as Nicotiana sylvestris 18, Citrus sinensis 1920, Avena fatua 21, Spinacia oleracea 22, Brassica campestris 23, Helianthus annuus 24, Pisum sativum 25, Lycopersicon esculentum 26, Arabidopsis thaliana 272829, Oryza sativa 30, Triticum aestivum 31, Panax ginseng 32, Populus trichocarpa 3334 and Thellungiella salsuginea 35, have been isolated and characterised. Unfortunately very few reports on genome-wide identification and characterisation of GPX family proteins to date have been reported.…”
mentioning
confidence: 99%
“…Other studies also found that the Panax ginseng exerts have antiproliferative effect for rat hepatocarcinogenesis [15], heat processing may be a useful method to enhance the anticancer effect [16]. Many scientists studied the Panax ginseng via the bioinformatics perspective [17,18], such as Yu-Jin Kim, et al explored that the related genes of Panax ginseng and their expression against environmental stresses [19]. Konstantin V. Kiselev, et al, tended to think that mutation of Panax ginseng genes may be happened during long-term cultivation [20].…”
Section: Introductionmentioning
confidence: 99%
“…10 Since then, more than 100 cDNAs encoding GPX proteins exhibiting high sequence similarity to animal GPXs have been isolated, cloned and characterized from various plant species. [11][12][13][14][15][16][17][18][19][20][21][22][23] Most GPX genes isolated from plants so far have highest sequence homology to animal phospholipid hydroperoxide glutathione peroxidase (PHGPX). Cit-SAP was the first naturally isolated PHGPX protein, partially purified from saltadapted citrus cells.…”
mentioning
confidence: 99%
“…37 Gene expression analysis has shown an increase in the levels of PHGPX mRNA in several plant species undergoing different biotic and abiotic stresses, such as pathogen infections, 10,14,38 high salt concentrations, 39,22 exposure to heavy metals, 40,41 mechanical stimulation, 16 aluminum toxicity, 42 seed germination, 12 salt and osmotic stress, 43 oxidative stress, 39,35 chilling stress. 22 PHGPXs may play dual roles as a redox transducer in addition to acting as a H 2 O 2 scavenger under stress. 33 Thus, PHGPX proteins may have different functions in plant cells, with some isoforms functioning in signal transduction pathway, while others are involved in catalyzing the reduction of harmful products formed by ROS.…”
mentioning
confidence: 99%